INFLUENCE OF SOCIAL MEDIA ON SUBSEQUENTLY CHANGING BEHAVIOUR IN YOUTH AND EFFECT OF SAME ON MENTAL HEALTH. - Mittal , Ashish Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
Introduction: Social media has become an integrated part of daily life, with an estimated 3 billion social media users worldwide. Adolescents and young adults are the most active users of social media. Research on social media has grown rapidly, with the potential association of social media use and mental health and well-being becoming a polarized and much-studied subject. The current body of knowledge on this theme is complex and difficult-to-follow. The current paper presents a scoping review of the published literature in the research field of social media use and its association with mental health and well-being among adolescents. Material and Method: The present study was conducted in Tertiary care hospital of north India. The goal of this quantitative correlation study was to assess the relationship between social media usage and perceived mental health issues among college students, which has been accomplished through the distribution of a survey to students. The technique used to study the impact of social media on youth was normative survey approach and its statistical evaluation which is a common technique to represent whole population. A selected age group of people from 15-18 years and 18- 25 years were choosing for analysis. The data was also separated on to the basis of gender where around girl: boy was obtained as 40:60 ratio. CONCLUSION: Social media is one of the quickest modes of communication, and it has a significant impact on the personal lifestyles of today’s youth. Though it has widespread popularity among young people, it also has some negative consequences, including concerns about privacy. Relying solely on social media reduces face-to-face communication and instead promotes cyber communication. KEYWORD: social media, mental health